Fish Oil Supplements Lower Serum Lipids and Glucose in Correlation with a Reduction in Plasma Fibroblast Growth Factor 21 and Prostaglandin E2 in Nonalcoholic Fatty Liver Disease Associated with Hyperlipidemia: A Randomized Clinical Trial. - Yu Qin; Yong Zhou; Shi-Hui Chen; Xiao-Lan Zhao; Li Ran; Xiang-Long Zeng; Ying Wu; Jun-Li Chen; Chao Kang; Fu-Rong Shu; Qian-Yong Zhang; Man-Tian Mi (PLoS ONE, 2015)
Fish oil has been used effectively in the treatment of cardiovascular disease via triglyceride reduction and inflammation modulation. This study aimed to assess the effects of fish oil on patients with nonalcoholic fatty liver disease (NAFLD) associated with hyperlipidemia. Eighty participants with NAFLD associated with hyperlipidemia were randomly assigned to consume fish oil (n=40, 4 g/d) or corn oil capsules (n=40, 4 g/d) for 3 months in a double-blind, randomized clinical trial. Blood levels of lipids, glucose and insulin, liver enzymes, kidney parameters and cytokines at baseline and the end of the study were measured. Seventy people finished the trial. Plasma concentrations of eicosapentaenoic acid and docosahexaenoic acid significantly increased in the fish oil group after intervention. After adjustment for age, gender and BMI, fish oil significantly decreased fasting serum concentrations of total cholesterol, triglyceride, apolipoprotein B and glucose (by (mean±SD) 0.49±0.43 mmol/L, 0.58±0.89 mmol/L, 0.28±0.33 g/L and 0.76±0.56 mmol/L, respectively, P<0.05), as well as alanine aminotransferase and γ-glutamyl transpeptidase levels (by (median (interquartile)) 9.0(0.5, 21.5) and 7.0(2.2, 20.0) IU/L, respectively, P<0.05), significantly increased serum adiponectin levels (by 1.29±0.62 μg/mL, P<0.001), and reduced serum levels of tumor necrosis factor α, leukotrienes B4, fibroblast growth factor 21 (FGF21), cytokeratin 18 fragment M30 and prostaglandin E2 (by 1.70±1.18 pg/mL, 0.59±0.28 ng/mL, 121±31 pg/mL, 83±60 IU/L and 10.9±2.3 pg/mL, respectively, P<0.001). Corn oil had no effect except for increasing serum creatinine concentrations by 7.7±8.9 μmol/L (P=0.008). The effects of fish oil on lipids, glucose and γ-glutamyl transpeptidase were positively correlated with the reductions of serum FGF21 and prostaglandin E2 concentrations after adjustment for age, gender and BMI (r = 0.275 to 0.360 and 0.261 to 0.375, respectively, P<0.05). In conclusion, our findings suggest that fish oil can benefit metabolic abnormalities associated with NAFLD treatment.ChiCTR-TRC-12002380.